Ethical decision-making about older adults and moral intensity: an international study of physicians. Issue 4 (28th March 2008) - Malloy, D C; Williams, J; Hadjistavropoulos, T; Krishnan, B; Jeyaraj, M; McCarthy, E F; Murakami, M; Paholpak, S; Mafukidze, J; Hillis, B
Abstract : Through discourse with international groups of physicians, we conducted a cross-cultural analysis of the types of ethical dilemmas physicians face. Qualitative analysis was used to categorise the dilemmas into seven themes, which we compared among the physicians by country of practice. These themes were a-theoretically-driven and grounded heavily within the text. We then subjected the dilemmas to an analysis of moral intensity, which represents an important (albeit novel within healthcare research) theoretical perspective of ethical decision making. These constructs (ie, culture and moral intensity) represent salient determinants of ethical behaviour and our cross-cultural sample afforded us the opportunity to consider both the pragmatic aspects of culture, as they are perceived by physicians, as well as the theory-driven concept of moral intensity. By examining both culture and moral intensity, we hope to better elucidate the complexities of ethical decision-making determinants among physicians in their daily practice. Doing so may potentially have practical implications for ethics training of medical students and foreign physicians.